Применение мембранных технологий для получения растворов "активного хлора" - Смирнов, А. А.; Диаб, Хассан Мусса; Тульский, Геннадий Георгиевич (НТУ "ХПИ", 2009)
Досліджено електрохімічний синтез водного розчину NaClO з концентрацією 80...120 г/дм³. Розглянуто можливість застосування мембранних технологій для одержання концентрованих розчинів "активного хлору". Запропоновано конструкцію електролізера, яка запобігає відновленню NaClO на катоді. Визначена концентрація хлориду натрію при робочій густині струму. Визначені технологічні показники електрохімічного синтезу.

The electrochemical synthesis of solution NaClO with concentration 800...120 г/дм³ has been researched. The application possibility membrane technology for reception of the concentrated solutions of "active chlorine" is considered. The design cell has been offered. It allows preventing recovery NaClO on the cathode is offered. Concentration of chloride of sodium is defined at working density of a current. Technological parameters of an electrochemical synthesis are established.
Keywords: мембранные электролизеры; ионообменные мембраны; диоксид хлора; дезинфекция; очистка сточных вод; обеззараживающее средство